Mining Intensity Effect of Coal Burst Induced by Ultra-Thick Composite Key Stratum Movement: an Experimental Study - Bai , Jinzheng; Zhang, Xiufeng; Dou, Linming; Gong, Siyuan; Cao, Anye; Miao, Leigang; Guo, Hongjun; Wang, Cunwen; Liu, Chuancheng (Archives of Mining Sciences, 2026)
Increasing mining intensity complicates overlying strata movement and elevates coal burst risk. However, the mechanism of coal burst initiation under the coupled response of displacement, stress, and vibration fields remains poorly understood. This study investigates a coal burst-prone mine in Northwest China characterised by compound key strata. Through laboratory experiments and theoretical analysis, the development of transverse and longitudinal fractures in the overburden induced by mining was examined. The mechanical mechanism of coal burst under varying mining intensities was revealed based on the response of the stress and vibration fields in the overburden. Results show that as mining intensity increases, overburden activity becomes more incomplete and the energy released by fracturing rises sharply. The voussoir beam structure at lower levels transforms into a high-level cantilever beam. Within the same advancing range, higher mining intensity reduces the frequency of roof weighting but increases the weighting interval and ultimate suspended roof length. The fracture range progressively extends upward. In terms of stress response magnitude and timing, the order is: high-level key stratum < mid-level key stratum < low-level key stratum. During low-speed mining, vibration signals are continuous, low-energy, and high-frequency, indicating progressive overburden failure. In contrast, rapid mining produces sudden, high-energy, and low-frequency signals, associated with large-scale roof suspension or sudden key stratum fracture. This study concludes that high-intensity mining intensifies both the degree and scope of overburden movement, significantly elevating static stress and dynamic fracturing loads. When these exceed a critical threshold, an overburden-type coal bursts are readily induced.